Let ˜γ be a horizontal lift of the curve γ:[0,1]→M on a principal bundle P(M,G), with the projection π:P→M. The parallel transport is defined by the map:
Γ(˜γ−1):π−1(γ(1))→π−1(γ(0))
where ˜γ−1(t)=˜γ(1−t). Apparently, this means that Γ(˜γ−1)=Γ(˜γ)−1, but I don't see how this is true. As far as I understand, equation (1) implies that:
Γ(˜γ):π−1(γ(1))→π−1(γ(0))
because Γ(˜γ) sends the fibre at t=0 (i.e.γ(1−0)=γ(1)) to the fibre at t=1 (i.e. γ(1−1)=γ(0)). But this is clearly wrong because it implies that Γ(˜γ−1)=Γ(˜γ)⟹Γ(˜γ−1)≠Γ(˜γ)−1. Anybody knows where I'm making a mistake?